Chinese Manufacturing and Agricultural Investment in Tanzania: A Scoping Study - Ying Xia (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2019)
Tanzania focus – In a three-part series comprising two working papers and a briefing paper, Ying Xia dives deep into the investments driving the manufacturing sector as well as agricultural investments in Kenya and Tanzania. While the briefing paper offers a honed-in look at the key takeaways, this working paper gives detailed insights into what the industry looks like on the ground in Tanzania.
Keywords: 330